Influence of dolls of reflecting the perfectionist woman’s body on the self-perception of the of 5-6 years old girls - AYSE ALPTEKIN; AYSEGUL SARIKAYA (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This research intends to look at how girls aged 5 and 6 feel about their own bodies in relation to the dolls that have become increasingly popular with girls in recent years and are seen as reflecting a perfectionist ideal of the female form that is seen as harmful to the development of children in some countries.Method: Data were gathered using a Turkish version of the